Clinical investigation on temporomandibular disorders in patients with paresthesia of the tongue - SUZUKI, Kazuhiko; SHIBUYA, Tomoaki; OHMURA, Yoshiaki; KINO, Koji; AMAGASA, Teruo; KOBAYASHI, Junji (Journal of the Japanese Society for the Temporomandibular Joint, 1995)
Isberg, et al (1987) reported lingual numbness and speech articulation impairment associated with temporomandibular joint disk displacement. They thought it occurred when the lingual nerve passes through the lower head of the lateral pterygoid muscle. TMD (temporomandibular disorder) patients were investigated in relation to paresthesia of the tongue by using TMD questionnaires in 1992. 18 of 503 TMD patients had an impairment in tongue sensitivity and 1 patient seemed to have the same symptoms as those in Isberg's report.